Pengembangan Aplikasi Pembelajaran Menulis Huruf Arab - Rochmansyah, Andi Yunindra; Sutanto, Teguh; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
In the learning process, there are several interrelated elements so that learning goes according to expectations. Among the essential elements that include the methods and instructional media. Two things that will affect the child's responses during and after the process of learning One of the main functions of the media is as a teaching aid and the conditions that influence learning environment organized and created by the teacher / parent. The process of learning to write Arabic letters are less interesting and complicated for children, in The Education of Al - Quran (TPA), is available in the form of instructional media writing arabic worksheets. Every child should have the worksheet itself, but usually children - as young as elementary school (SD) meets worksheet with graffiti - graffiti or writings are not necessarily in accordance with the instructions write the Arabic alphabet. To address the problems that occurred in the process of learning how to write the Arabic alphabet built an android-based application that can help children to learn how to write the Arabic alphabet with more fun in interactive media. With this application so a child can understand and implement the steps to write the Arabic alphabet correctly. Applications can also save the results of every child to learn to write for use as an evaluation process for parents or teachers to guide. Keywords: Android, Arabic letters, SurfaceView, Writing.